Adsorption of gas molecules of CH4, CO and H2O on the vanadium dioxide monolayer: computational method and model. (5th November 2020) - Lin, Long; Chen, Ruixin; Huang, Jingtao; Wang, Pengtao; Tao, Hualong; Zhang, Zhanying
Abstract: Inspired by the recent use of two-dimensional nanomaterials as gas sensors, we used density functional theory calculations to study the adsorption of gas molecules (CH4, CO and H2 O) on sandwich vanadium dioxide tablets. The results showed that of all these gases, only the CH4 gas molecule was the electron acceptor with significant charge transfer on the VO2 sheet. The adsorption energies of CH4, CO and H2 O are −229.5 meV, −239.1 meV and −388.3 meV, respectively. We have also compared the adsorption energy of three different gas molecules on the VO2 surface, our calculation results show that when the three kinds of gases are adsorbed on the VO2 surface, the order of the surface adsorption energy is H2 O > CO > CH4 . It is also found that after adsorption of CH4, CO and H2 O molecules, the electronic properties of VO2 sheet changed obviously. However, due to the strong adsorption of H2 O molecule on VO2 sheet, it is difficult to desorption, which hinders its application in gas molecular sensors. The optical properties of VO2 sheet are further calculated. The absorption of CH4, CO and H2 O molecules is introduced to red-shift the dielectric function of the thin film, which indicates that the optical properties of the thin film have changed significantly. According to the change of optical properties of VO2 sheet before and after molecular adsorption, VO2 can be used as a highly selective optical gas sensor for CH4, CO and H2 O detection. These results provide a new approach for the potential application of VO2 based optical gas sensors.